Pengolahan Bisnis Catering Ummi Nisa Medan Berbasis Web - Khairunnisa Khairunnisa; Fera Damayanti (Program Studi Sistem Informasi, 2018)
Catering Ummi Nisa is a business that runs its business in the field of food services in Medan. From a manual sales system by distributing flyers on the street, in community homes look less effective. With development of technology that is growing rapidly, internet technology has reliable every community, especially in sales and information. So much-needed changes to improve the ordering and sales system are communicative and informative. With this change researches have a goal to creat Ummi Nisa Catering website so that this business can grow more widely. With the customer website will be easier to find the information needed. Any product information and menu offered on Catering Ummi Nisa would be obtained on the website. In addition to customer information is also able to order Catering Online, so that sales Catering Ummi Nisa more effective and efficient in business. This is very beneficial to catering owner and customers.Keywords: Information System, Online, Sales, Food, Website